Structural and Optical Properties of Ba0.7Dy0.3Fe11.4Cr0.6O19/Polyaniline (PANI) Nanocomposites for Optoelectronics. (May 2020) - Tchouank Tekou, Carol T.; Mohammed, J.; Mukhtar, G.; Halilu, N.; Getso, R. S.; Abdullahi, Z. H.; Basandrai, D.; Srivastava, A. K.
Abstract: M-type hexaferrites have found considerable application in microwave absorption and magnetic recording. Sol-gel auto-combustion technique was utilized to prepare Ba0.7 Dy0.3 Fe11.4 Cr0.6 O19 nano-sized particles which were sintered at 1000 °C for 6 hours. XRD patterns of the prepared sample show magnetoplumbite phase of M-type hexaferrite along with the presence of hematite (α-Fe2 O3 ) and polyaniline. Two specific bands in the range 400-600 cm −1 were observed in the FTIR spectra signifying the formation of hexaferrites structure. The peaks corresponding to polyaniline are also present in the FTIR spectra in the range 800-1600 cm −1 . FESEM analysis shows grains with shape similar to hexagonal plate embedded on the surface of polyaniline. The band gap was found to decrease from 1.96 eV to 1.59 eV.